A trauma-informed approach to library services - Tolley, Rebecca, 1971- (ALA Editions, 2020)
We are only now coming to terms with how common trauma really is; a landmark Kaiser study that surveyed patients receiving physicals found that almost two-thirds had experienced at least one form of abuse, neglect, or other trauma as a child. Though originating in the fields of health and social services, trauma-Informed care is a framework that holds great promise for application to library work. Empathetic service, positive patron encounters, and a more trusting workplace are only a few of the benefits that this approach offers. In this important book Tolley, experienced in both academic and public libraries, puts these ideas into the library context. Library administrators, directors, and reference and user services staff will all benefit from learning the six key principles of trauma-informed care; characteristics of a trusting and transparent library organization, plus discussion questions to promote a sense of psychological safety among library workers; how certain language and labels can undermine mutuality, with suggested phrases that will help library staff demonstrate neutrality to patron ideas and views during information requests; delivery models that empower patrons; advice on balancing free speech on campus with students' need for safety; how proper furniture arrangement can help people suffering from PTSD feel safe; guidance on creating safe zones for LGBTQIA+ children, teens, and adults; and self-assessment tools to support change toward trauma-responsive library services. Using the trauma-informed approach outlined in this book, libraries can ensure they are empathetic community hubs where everyone feels welcomed, respected, and safe. --